An Assessment of the Contribution of Credit Reference Bureau Regulation towards Mitigating Credit Risks in the Kenya`s Banking Industry - Marangu, Wilfred N.; Shisia, Adam; Omwario, Ben (My University, 2014)
In Kenya, the use of Credit Reference Bureaus to mitigate credit risks is a new concept. The purpose of this study was to carry out an analysis on the contribution of credit reference bureaus in preventing credit risks in Kenya’s financial sector. This study also sought to evaluate the extent to which credit reference bureaus regulation has been implemented by commercial banks and to establish any challenges facing credit reference bureaus in Kenya. In chapter three, the case study approach using descriptive design that investigated the concept of applying credit reference bureau in the prevention of credit risks was used. Questionnaires and interviews as instrument of data collection were used. Data was analyzed by SPSS computer program and presented by use of tables, percentages and figures. A regression relationship was generated to show the extent to which each dependent variable was influenced by the independent variable. This was shown by the coefficient of the independent variable in each case. A correlation analysis was also performed to find how the variables are related to each other in the model. The research findings in chapter four found out that the Credit Reference Bureaus concept contributes towards reduction of credit risks and that implementation of Credit Reference Bureaus regulation has gained general acceptance substantially in Kenya. The study also revealed that lack of awareness and non-compliance are currently the major challenges of Credit Reference Bureaus regulation in Kenya. In chapter five, the study recommends that the Credit Reference Bureaus regulation be extended to all sectors that handle credit transactions. There is need for our present Credit Reference Bureaus firms to link with other regional Credit Reference Bureaus firms in other countries. The study further recommends that membership to the Credit Reference Bureaus should be mandatory and enforceable and awareness campaigns to sensitize the public and companies that offer credit transactions should be carried out by the stakeholders.
Keywords: Credit Reference Bureaus; Credit Risk; Kenya’s Banking Industry